3D climate modeling of Earth-like extrasolar planets orbiting different types of host stars. (June 2015) - Godolt, M.; Grenfell, J.L.; Hamann-Reinus, A.; Kitzmann, D.; Kunze, M.; Langematz, U.; von Paris, P.; Patzer, A.B.C.; Rauer, H.; Stracke, B.
Abstract: The potential habitability of a terrestrial planet is usually defined by the possible existence of liquid water on its surface, since life as we know it needs liquid water at least during a part of its life cycle. The potential presence of liquid water on a planetary surface depends on many factors such as, most importantly, surface temperatures. The properties of the planetary atmosphere and its interaction with the radiative energy provided by the planet's host star are thereby of decisive importance. In this study we investigate the influence of different main-sequence stars (F, G, and K-type stars) upon the climate of Earth-like extrasolar planets and their potential habitability by applying a state-of-the-art three-dimensional (3D) Earth climate model accounting for local and dynamical processes. The calculations have been performed for planets with Earth-like atmospheres at orbital distances (and corresponding orbital periods) where the total amount of energy received from the various host stars equals the solar constant. In contrast to previous 3D modeling studies, we include the effect of ozone radiative heating upon the vertical temperature structure of the atmospheres. The global orbital mean results obtained have been compared to those of a one-dimensional (1D) radiative convective climate model to investigate the approximation of global mean 3D results by those of 1D models. The different stellar spectral energy distributions lead to different surface temperatures and due to ozone heating to very different vertical temperature structures. As previous 1D studies we find higher surface temperatures for the Earth-like planet around the K-type star, and lower temperatures for the planet around the F-type star compared to an Earth-like planet around the Sun. However, this effect is more pronounced in the 3D model results than in the 1D model because the 3D model accounts for feedback processes such as the ice-albedo and the water vapor feedback. Whether the 1D model may approximate the global mean of the 3D model results strongly depends on the choice of the relative humidity profile in the 1D model, which is used to determine the water vapor profile. Hence, possible changes in the hydrological cycle need to be accounted for when estimating the potential habitability of an extrasolar planet. Abstract : Highlights: We study Earth-like exoplanets around different host stars using a 3D climate model. We include the impact of ozone heating upon the vertical temperature structures. The effect of the stellar radiation is amplified by climate feedbacks. For the planet around the K-type star we find a change in the hydrological cycle. The global mean results of the 3D model may be approximated by the 1D model applied.